Pengaruh Gender Diversity, Kepemilikan Manajerial, dan Kepemilikan Publik terhadap Nilai Perusahaan - I Kadek Dida Ari Saputra; Ni Putu Budiadnyani (Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2026)
Firm value reflects investors’ perceptions of a company’s performance and future prospects. However, improvements in financial performance are not always followed by increases in firm value, particularly in manufacturing companies listed on the Indonesia Stock Exchange. This phenomenon indicates that non-financial factors may also play an important role. This study aims to examine the effect of gender diversity, managerial ownership, and public ownership on firm value. The research employs a quantitative causal approach using secondary data obtained from annual reports of manufacturing companies listed on the Indonesia Stock Exchange during the 2021–2024 period. The sample was selected using purposive sampling, resulting in 29 companies with 116 observations. Data were analyzed using multiple linear regression after passing classical assumption tests. Firm value is measured using Price to Book Value, while gender diversity is measured by the proportion of female directors, managerial ownership by the percentage of shares owned by management, and public ownership by the percentage of shares owned by the public. The results of this study are expected to provide empirical evidence regarding the role of corporate governance and ownership structure as signals that influence firm value, as well as practical implications for management, investors, and regulators in enhancing firm value.